Interaction between lamellar twinning and catalyst dynamics in spontaneous core–shell InGaP nanowires. Issue 29 (8th July 2015) - Oliveira, D. S.; Tizei, L. H. G.; Li, A.; Vasconcelos, T. L.; Senna, C. A.; Archanjo, B. S.; Ugarte, D.; Cotta, M. A.
Abstract : Micron-long <211>-oriented III–V nanowires are made possible due to lamellar twinning and stacking faults which stabilize the {111}A facet at the catalyst–nanowire interface. Abstract : Semiconductor nanowires oriented along the [211] direction usually present twins parallel to their axis. For group IV nanowires this kind of twin allows the formation of a catalyst–nanowire interface composed of two equivalent {111} facets. For III–V nanowires, however, the twin will generate two facets with different polarities. In order to keep the <211> orientation stable, a balance in growth rates for these different facets must be reached. We report here the observation of stable, micron-long <211>-oriented InGaP nanowires with a spontaneous core–shell structure. We show that stacking fault formation in the crystal region corresponding to the {111}A facet termination provides a stable NW/NP interface for growth along the <211> direction. During sample cool down, however, the catalyst migrates to a lateral {111}B facet, allowing the growth of branches perpendicular to the initial orientation. In addition to that, we show that the core–shell structure is non-concentric, most likely due to the asymmetry between the facets formed in the NW sidewall; this effect generates stress along the nanowire, which can be relieved through bending.